-a+c+3-c=-a+3
x+y+7-x+y=7+2y
-15+3c+3c-5=-20+6c
-2x+2a+4
5+x-x+5=10
6-a-x-3+a+x=3
Пошаговое объяснение:
-(a - c) + (3 - с)= -a + c + 3 - c = -a + 3
(х + y +7) - (х - у)= x + y + 7 - x + y = 2y + 7
-3(5 – с) + Зc - 5= -15 + 3c + 3c - 5 = 6c - 20
-2 (x — а — 2)= -2x + 2a + 4
(5 + х) - (х – 5)= 5 + x - x + 5 = 10
6 — а — x — (3 – а – x)= 6 - a - x - 3 + a + x = 3
-a+c+3-c=-a+3
x+y+7-x+y=7+2y
-15+3c+3c-5=-20+6c
-2x+2a+4
5+x-x+5=10
6-a-x-3+a+x=3
Пошаговое объяснение:
-(a - c) + (3 - с)= -a + c + 3 - c = -a + 3
(х + y +7) - (х - у)= x + y + 7 - x + y = 2y + 7
-3(5 – с) + Зc - 5= -15 + 3c + 3c - 5 = 6c - 20
-2 (x — а — 2)= -2x + 2a + 4
(5 + х) - (х – 5)= 5 + x - x + 5 = 10
6 — а — x — (3 – а – x)= 6 - a - x - 3 + a + x = 3